Activity Test Of Ethanol Extract Of Green Sugarcane Stem (Saccharum Officinarum Linn) As Antidiabetic In Male Mice - Prihardini Prihardini; Dewy Resty Basuki; Rosa Juwita Hesturini (Jurnal EduHealth, 2023)
Diabetes Mellitus is a metabolic disorder characterized by an increase in blood sugar levels caused by the body's inability to produce insulin. One of the non-pharmacological therapies is by utilizing herbal plants such as green sugarcane stalks (Saccarum officinarum L.). Research objective: to find out whether administration of green sugarcane stem extract can reduce alloxan-induced blood glucose levels in mice. Research method: experimental using male males as test animals totaling 25 animals which were divided into 5 groups, namely the negative control group, positive control, a sample group of 100 mg/kg, 125 mg/kg, and 250 mg/kg. Data were analyzed by one-way ANOVA test and continued with the LSD test. The results of the study at a dose of 125 mg/kg BW optimally reduce blood glucose level.